Rancang Bangun Sistem Deteksi Dan Perhitungan Jumlah Orang Menggunakan Metode Convolutional Neural Network (CNN) - Indana Nihayatul Husna; Miftachul Ulum; Adi Kurniawan Saputro; Haryanto; Deni Tri Laksono; 6Dian Neipa Purnamasari (FORTEI Regional VII Jawa Timur, 2022)
Currently, technology is progressing very rapidly in various fields. One area of ​​technology that is multiplying is the field of electronics. Everyone wants a comfortable and straightforward process in every activity. Indoor people counting is developing as a novelty in video surveillance. Generally, security monitoring systems use CCTV cameras. The use of cameras can be used for monitoring the number of people (people counter). The working principle of this tool is to detect objects in the room that are processed by the camera. The camera will then be processed using the CNN (Convolutional Neural Network) algorithm to detect and count the number of people in the room based on the images of people's faces and or heads. To detect images of people's faces and heads using selective search to obtain image regions which are then used as CNN input. In this case, the region is used to determine the possibility of object images. The results of the classification calculation of the number of people from the CNN method will later be forwarded to the GUI to process data using Visual Studio Code. From the processing of data from the GUI, then the data will be displayed on the monitor.